Шесть дней июля: о Г. Д. Гае / В. Г. Новохатко - Новохатко В. Г. (Герои Советской Родины, 1987)
Экземпляры: ф.3 (ретро) / Инвентарный номер: 16769 / Сис.шифр: 63.3(2)61 / Авт.знак: Н 76 / ББК: 63.3(2)612.8